Comparisons of Nutrient Intakes and Diet Quality among Water-Based Beverage Consumers - Barraj, Leila M. (Nutrients, 2019)
Americans are encouraged to reduce intake of sugar-sweetened beverages (SSB). Zero and low-calorie water-based beverages can provide alternative options to SSB, though limited data are available to understand measures of diet quality across different beverage consumer groups. The purpose of this cross-sectional study was to quantify intake of added sugars, total sugars, carbohydrates, and diet quality among consumers of zero-calorie unsweetened beverages (ZCUB) compared to SSB; and, separately, among consumers of low- and no-calorie sweetened beverages (LNCSB) when compared to SSB. Dietary data from the 2009–2016 National Health and Nutrition Examination Survey (NHANES) were analyzed among three life stages by SSB, ZCUB, and LNCSB consumer groups and adjusted for participant characteristics and energy intake. Across all life stages, ZCUB and LNCSB consumers had lower mean intakes of total sugars, added sugars, and carbohydrates when compared to SSB consumers. Diet quality as measured by the Healthy Eating Index 2015 (HEI-2015) was also higher among ZCUB and LNCSB consumers compared to SSB consumers in analyses adjusted for participant characteristics. These results indicate that reduction of SSB from dietary patterns and replacement with ZCUB or LNCSB could help Americans improve overall diet quality.